Let x = cost of one t-shirt
Let y = cost of one sweatshirt
Jayden: 9x + 3y = $420
Carson: x + 6y = $296. Multiply Jayden's equation by -2
Jayden: -18x - 6y = $-840
Carson: x + 6y = $296. Add the equations together to eliminate variable y.
New equation: -17x = $-544. Divide each side by -17.
x = $32. Plug this value into one of the original equations.
32 + 6y = $296. Subtract 32 from each side.
6y = 264. Divide each side by 6.
y = 44.
Plug both your x and y value into one of the equations to ensure they're correct.
9(32) + 3(44) = 420
420 = 420.
x = 32
y = 44.